Evaluación de la funcionalidad y resistencia osmótica del esparmatozoide ys u capacidad predictiva de la fertilidad en campo en porcinos - Belalcázar, Dyanne Alejandra (Universidad Antonio Nariño, 2023)
The prediction of pregnancy within the pig field can be given, from the application of a laboratory technique consisting of the combination of sHOST, marking with pi/Fitc-Pna and fixation with formolate solution, which allows to easily distinguish and quantify the Functionally Competent Spermatozoa (EFC), that is: alive, with biochemical functionality of the membrane, with acrosomic resistance, without abnormality of head and intermediate tract, without cytoplasmic drops and not agglutinated. The combination of sHOST and marking with PI and FITC-PNA allows evidence of the proportion of living cells, with membrane functionality and acrosomic resistance after osmotic stress; and fixation with formolade solution allows to show sperm with abnormal shapes. Laboratory analyses were performed on 14 ejaculate samples from different pig farms nationwide, allowing analysis of sperm functionality by hypoosmotic stress and evaluation of membrane integrity, using a correlation with births of inseminated breeding females, using a statistical analysis, with a pregnancy rate of 14.62% and an average effectiveness of 90% in 45 pregnant females, with a loss of 3 females or 0 births equivalent to 6% of all females. The main conclusion being that the pregnancy rate of females in the pig field cannot be predicted from a laboratory analysis of ejaculates, keeping the seminal liquid frozen at an average temperature of 16 °C and taking it to a laboratory procedure up to a temperature of 34 °C, as CFEs showed a trend in relation to the number of total piglets born, but this was not significant and it is therefore recommended to increase the number of samples to corroborate information.